ANALYSIS PUBLIC HOUSING MANAGEMENT (CASE STUDI: PUBLIC HOUSING KS TUBUN, WEST JAKARTA) - N. Dhea Madinah Al Qibthia; Yayah Awaliyah; Flandi Tito Pratama (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The government’s efforts to overcome the problem of the need for livable housing for the community, one of which is the rusunawa program providing decent housing for the community, especially low-income people (MBR). This study aims to analyze and explains how the rules related to the management of Rusunawa KS Tubun in West Jakarta. The method of analysis is qualitative using a linear responsibility chart, with secondary data collection sourced from literature reviews, data agencies, relevant policy regulations, and infrastructure management best practices. Based on the results of the analysis, it is found that the stakeholders involved and responsible for the process of implementing the activities include DKI Jakarta Provincial Government, assistants (private sector, consultants, and NGOs), UPS who are directly involved in the management of the rusunawa and community involvement from the organizational stages of the tower management, care, and maintenance, financial management, conflict management, residential, legal to community development. The results of the linear responsibility diagram: the management of Rusunawa KS Tubun can be directed to the implementation of Singapore Public Housing management as key factors for the government and stakeholders in increasing the success of public housing policies.